Negotiating Inheritance Rights for Adopted Children: A Socio-Legal Study of Islamic Law and Local Practices - Muhammad Zainul Syafaat; Musarrifatur Rachmah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2026)
This study discusses the position of adopted children in the Islamic inheritance system and social practices. The background of the research arises from the incompatibility between Islamic legal norms, which place adopted children outside their inheritance rights because they lack a relationship of nasab, and the community's social practices, which tend to grant property to adopted children based on contributions and emotional closeness. The purpose of the research is to analyze how Islamic law is implemented in local practice, understand the mechanism of wealth allocation, and evaluate the interaction between formal law and social values. The research uses a qualitative-empirical approach with data collection through semi-structured interviews, field observations, and documentation of Islamic legal literature. The study found that adopted children acquire property through compulsory wills, grants, or direct distribution, reflecting the flexibility of Islamic law and the principle of substantive justice. In conclusion, Islamic law can adapt to social context without altering the principle of nasab, while society upholds social justice through formal and informal mechanisms. This research makes a theoretical and practical contribution to socio-legal studies, highlighting the harmonization between sharia norms and local practices that are oriented towards benefit.